Analysis of the Acute Cytokine Dynamics Induced in Professional Padel According to the Playing Side of the Court and Sex-Related Differences - María Pía Cádiz-Gallardo; Francisco Pradas; Pamela Patanè; Alejandro García-Giménez; Miguel Lecina; Luis Carrasco (Metabolites, 2025)
Background/Objectives: Moderate-intensity physical exercise induces an anti-inflammatory state that may help prevent or manage various diseases. In contrast, high-intensity exercise is closely associated with systemic inflammation, which can lead to immunosuppression, especially when recovery periods are too short, reduced sports performance and potential health risks for the athlete. This study aimed to analyze the acute cytokine dynamics in professional padel players, focusing on differences related to the side of play on the court (forehand or backhand) and sex. Methods: A total of 21 elite padel players (11 females and 10 males; age: 27.7 ± 6.3 y) voluntarily participated in the study. Pro-inflammatory cytokines (interleukin (IL)-1ß, IL-2, IL-5, IL-6, IL-7, IL-8, IL-12, tumor necrosis factor alpha and interferon gamma) and anti-inflammatory cytokines (IL-5, IL-6, IL-10, IL-13) were analyzed before and after a padel match. Results: The results showed significant changes in pro- and anti-inflammatory, including a decrease in IL-7 (p = 0.02), an increase in IL-8 (p ≤ 0.001) and an increase in IL-10 (p = 0.001). No significant differences were observed based on the side of play on the court, suggesting that this variable does not influence the immune response. Conclusions: Competitive padel at an elite level elicits an anti-inflammatory response, characterized by an increase in IL-10 and a reduction in pro-inflammatory cytokines. This response highlights the potential health benefits of padel as a moderate-intensity sport, particularly in managing systemic inflammation.